High risk of unsuccessful treatment outcome in migrant population with tuberculosis: Data from three Italian hospitals - Francesco Di Gennaro; Sergio Cotugno; Massimo Fasano; Aurelia Ricciardi; Luigi Ronga; Rossana Lattanzio; Anna Grimaldi; Davide Fiore Bavaro; Marianna Ciarallo; Stefania Garzone; Giuseppina De Iaco; Giacomo Guido; et al. (Frontiers Media S.A., 2023)
IntroductionTuberculosis (TB) remains an unresolved global health problem and vulnerable groups such as migrants remain the most affected with a higher risk of worse outcomes. The aim of this study was to evaluate clinical features, outcomes, and adverse events in migrant and native Italian patients admitted to three Italian hospitals in Southern Italy in order to assess differences and targeted strategies.MethodsWe performed a retrospective study on TB patients admitted between January 1, 2013, and December 31, 2021, in three Apulia hospitals. Two logistic regression models were used, with the dependent variables being (I) unsuccessful treatment (died, loss to follow-up, and failed treatment) and (II) adverse events.ResultsWe enrolled 543 consecutive patients admitted at three Italian hospitals with a diagnosis of TB during the study period, of them 323 (59.5%) were migrants and 220 Italian patients. The treatment success rate in the migrant group was 44.9% (137/305), while in the non-migrant group was 97.1% (203/209). Independent factors of unsuccess treatment (death, failure or loss to follow up) were: migrant status (O.R. = 11.31; 95% CI 9.72-14.23), being male (O.R. = 4.63; 95% CI 2.16-6.10), homelessness (O.R. = 3.23; 95% CI 2.58-4.54), having a MDR (Multidrug-resistant) (O.R = 6.44; 95% CI 4.74-8.23), diagnostic delay (O.R. = 3.55; 95% CI 1.98-5.67), and length of hospitalization (O.R. = 3.43; 95% CI 1.88-5.87). While, age >65 ys (O.R. = 3.11; 95% CI 1.42-4.76), presence of extrapulmonary TB (O.R. = 1.51; 95% CI 1.31-2.18), monoresistance (O.R. = 1.45; 95% CI 1.25-3.14) and MDR pattern (O.R. = 2.44; 95% CI 1.74-5.03) resulted associated with adverse events.ConclusionMigrant population is at high risk of unsuccessful treatment (death, loss to follow-up, and treatment failure). Policies targeted specifically to this group are needed to really impact and improve their health status and also to contain the TB burden.